REVIEW ARTIKEL: POTENSI LIDAH BUAYA (Aloe vera (L.) Burm. f.) SEBAGAI BAHAN DASAR PEMBUATAN EDIBLE FILM/COATING - Mayang, Julia Agustin; Pasaribu, Subur P.; Panggabean, Aman Sentosa (PROSIDING SEMINAR KIMIA, 2024)
Plastic is a very common packaging material in the food industry, due to its practicality, durability, and flexibility. However, its negative impact on the environment has prompted efforts to find more environmentally friendly alternatives. One promising solution is the development of edible films and coatings, which are made from edible materials and have biodegradable properties. Aloe vera has become an interesting material in the development of edible films and coatings due to its beneficial active compounds. This article conducts a review of the existing literature on the manufacture of aloe vera-based edible films and coatings. The literature review method was used to collect relevant information from various online sources. The results showed that aloe vera edible films and coatings have great potential in food packaging, because they are not only environmentally friendly and edible, but can also improve the quality and shelf life of food products. With the addition of additional ingredients such as gelatin, chitosan, starch, alginate, PVA, and CMC, the antimicrobial, antioxidant, and antifungal properties of the films and coatings can be enhanced. The use of aloe vera edible coatings has also been shown to affect the chemical, physical, and sensory properties of coated food products. In conclusion, the use of edible films and aloe vera coatings is promising as a sustainable alternative in food packaging, as they can increase protection of food products without compromising product safety or quality. Keywords : Aloe vera (L.) Burm.f.), edible films, edible coatings